NEW DIRECTIONS IN THE ROLLED WIRE DEVELOPMENT - A. V. Vedeneev (Литьë и металлургия, 2004)
Analysis of the world practice and comparison with the competitors data shows, that for keeping up of RUP “BMZ'' competitiveness it is necessary to carry out works in directions of perfection of the steel wire cord production technology, development of steel wire cord, development of the breaker constructions with the high infiltration of rubber of wire with superstandard diameter and etc.